2006
DOI: 10.1227/01.neu.0000192162.99567.96
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Stimulation in Treatment of Chronic Benign Pain: Challenges in Treatment Planning and Present Status, a 22-Year Experience

Abstract: Spinal cord stimulation can provide significant long-term pain relief with improved quality of life and employment. Results of this study will be effective in better defining prognostic factors and reducing complications leading to higher success rates with spinal cord stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
403
3
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 429 publications
(435 citation statements)
references
References 58 publications
23
403
3
6
Order By: Relevance
“…The decision tree model was extended by a Markov model used to determine the cost and health outcomes over a 15-year time horizon. This time horizon was taken from the observational study conducted by Kumar et al 113 that presents a Kaplan-Meier survival curve that illustrates subsequent gradual loss of pain control during a 15-year period. Taylor and Taylor first used this model structure to evaluate the cost-effectiveness of SCS compared to CMM.…”
Section: Neuropathic Painmentioning
confidence: 99%
See 3 more Smart Citations
“…The decision tree model was extended by a Markov model used to determine the cost and health outcomes over a 15-year time horizon. This time horizon was taken from the observational study conducted by Kumar et al 113 that presents a Kaplan-Meier survival curve that illustrates subsequent gradual loss of pain control during a 15-year period. Taylor and Taylor first used this model structure to evaluate the cost-effectiveness of SCS compared to CMM.…”
Section: Neuropathic Painmentioning
confidence: 99%
“…According to the 22-year follow-up SCS study conducted by Kumar et al, 113 complications were the result of fractured electrodes, displaced electrodes, hardware malfunctions, biological factors or infections. Taylor et al 49 conducted a systematic review for chronic back and leg pain and FBSS.…”
Section: Long-term Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Kumar et al [11] compared SCS with conventional medical management and found SCS to be statistically superior in achieving more than 50 % pain relief (37 % in the SCS group vs 2 % in the conventional medical management group). Kumar et al [12] also determined in another study that SCS was effective in providing pain relief over both the short term and the long term, with a follow-up period of 97.6 months. In 2011, North et al [13 •• ] published the protocol for the ongoing EVI-DENCE study.…”
Section: Failed Back Surgery Syndromementioning
confidence: 97%